Synthesis and multifunctional applications of ZnO-rGO composite in gas sensor and supercapacitor - Patel A.; Shukla P.S.; Singh P.; Varma G.D. (My University, 2025)
Zinc Oxide (ZnO) nanoparticles and reduced graphene oxide (rGO) nanosheets were synthesized using the Coprecipitation method and modified Hummer’s method, respectively. The nanocomposite of ZnO@rGO was then prepared via the ultrasonication method for NO2 gas sensing and as an electrode material for supercapacitor application. The ZnO@rGO films with different rGO compositions of 12 weight percentage (wt. %) (ZG-12), 15 wt. % (ZG-15), and 18 wt. % (ZG-18) exhibited percentage responses of 46%, 60%, and 51% at room temperature for 10 ppm NO2 gas. Similarly, these composite materials exhibited specific capacitance values of 233, 253, and 207 Fg-1, respectively, at a specific current of 0.5 Ag-1. Gas-sensing performance was optimized under various conditions (0.5–40 ppm gas concentrations, 25–100 °C temperatures, and 25–100% relative humidity). The sensor demonstrated excellent NO2 gas selectivity, with a detection limit of 0.5 ppm. This ZnO-rGO-based NO2 gas sensor offers a novel, room temperature-operating device with high response, reproducibility, and humidity tolerance. An asymmetric supercapacitor (ASC) device is fabricated using ZG-15 as the cathode and rGO as the anode electrode. This ASC device demonstrates a commendable specific energy density of 5.34 Wh kg−1 and a power density of 2.20 kW kg−1. Moreover, two such devices connected in series successfully illuminate red and green LEDs for over 5 and 3 min, respectively. This work provided successful insight into the multifunctional application of ZnO@rGO composite in the field of gas sensing and energy storage devices. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2025.